Tingkat Stress Akademik Siswa SMA Pada Pembelajaran Biologi - Saputri, Nova Vivi Clara; Salsabila, Azura; Rohimah, Tina Rizqiyati; Rahmat, Adi (BIOEDUSCIENCE, 2024)
Background: Learning biology has material and concepts that must be understood by students, besides that there is material that is abstract in nature which makes students feel difficult in understanding it. This can cause student academic stress during the biology learning process. Students who experience stress will certainly feel a loss in the field of learning if they are not able to manage stress quickly and adequately. This research was conducted by analyzing the level of academic stress caused by five factors, namely motivation, self-confidence, anxiety, the education system, and teachers. Academic stress experienced by students is then categorized into three categories, namely mild stress, moderate stress, and severe stress. Methods: The research method used was a survey (expost facto) with instruments in the form of a questionnaire with nine choice scales and interviews. The population in this study were teenage students aged 16-18 years with a sample of 54 students from 3 schools with certain characteristics. Results: The results showed that students experienced academic stress caused by five factors, but with different categories. Students who experience academic stress in the severe category are generally caused by factors of motivation, self-confidence, the education system and teachers. Conclusion: While the anxiety factor only causes academic stress in the mild and moderate categories.